An Emerging Natural Gas Hub in the Eastern Mediterranean - Huurdeman, Alexander (World Bank, Washington, DC, 2020)
In January 2020, the energy ministers of seven countries and territories established the Eastern Mediterranean Gas Forum. EMGF’s objective is cooperation to overcome obstacles to exploitation of the region’s gas resources. Major challenges are (i) lowering the cost of supplying eastern Mediterranean gas in regional and international markets, and (ii) opening markets to enable hub operations and price discovery. The World Bank is supporting efforts to meet the second challenge and, in so doing, to meet the first as well.